EDUCATING CHILDREN THROUGH FAIRYTALES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Ustozlar uchun, 2026)
Spiritual and moral education of preschool children through fairy tale therapy, as well as teaching them national customs, traditions, historical and spiritual heritage, rich in educational opportunities, the formation and development of basic knowledge, skills and abilities in preparation for school. reflected in the article.